2009
DOI: 10.1210/jc.2008-1982
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dehydroepiandrosterone Therapy on Pubic Hair Growth and Psychological Well-Being in Adolescent Girls and Young Women with Central Adrenal Insufficiency: A Double-Blind, Randomized, Placebo-Controlled Phase III Trial

Abstract: In adolescent girls with central adrenal insufficiency, daily replacement with 25 mg DHEA orally is beneficial: atrichia pubis vanishes, and psychological well-being improves significantly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 29 publications
(37 reference statements)
1
30
0
Order By: Relevance
“…In this study, the daily co-administration of 50 mg DHEA did not give rise to safety concerns, as supported by data from the literature [54][55][56][57][58][59][60][61]. As demonstrated also in this study…”
Section: Accepted M Manuscriptsupporting
confidence: 88%
“…In this study, the daily co-administration of 50 mg DHEA did not give rise to safety concerns, as supported by data from the literature [54][55][56][57][58][59][60][61]. As demonstrated also in this study…”
Section: Accepted M Manuscriptsupporting
confidence: 88%
“…DHEA/S is implicated in the development of human pubic hair (Binder et al 2009), sweat and sebaceous glands (Stewart et al 1992), and elements of the hair follicle, as well as the skin (Thiboutot et al 2003). DHEAS is also found in axillary sweat (Labows et al 1979).…”
Section: Social Signals Of Middle Childhoodmentioning
confidence: 99%
“…Binder et al [19] reported that atrichia pubis vanishes and psychological well-being improves significantly by daily replacement with 25 mg DHEA orally in adolescent girls with central adrenal insufficiency.…”
Section: Introductionmentioning
confidence: 99%